Design and Implementation of Remote Medical Health Monitoring System - Patel, Mordhwaj; Narde, Rounak Singh; Shivnatri, Vinayshree; Pavankumar, B. S. N.; Chakraborty, Sujay (TIIEC 2013 : proceedings, 2013 Texas Instruments India Educators’ Conference : 4-5 April 2013, Bangalore, Karnataka, India, 2013)
The project relates to a health monitoring system comprising of a medical diagnosis done by a medically-qualified person in relation to a patient who is being monitored remotely via a communication system. The project is characterized in such a way that the medically-qualified person links medical data to health actions in a server using surveillance rules. The project is further characterized in which the server programs a remote terminal which is located close to the patient, such that the remote terminal uses an automatism which applies the surveillance rules to the medical data supplied to the terminal by at least one sensor which is associated with the patient by a machine interface. Thus the monitoring system proposed in the paper suffices the health concerns and adds more flexibility, ease of access and also adds the afford ability as well as feasibility of the solution proposed due to its cheap and robust design. Hence the system is quite apt for the implementation in the village areas where especially the health problems are more prominent and so they need to be given special attention.